INSECT PEST COMPLEX OF PEACROP (PISUM SATIVUM LINN.) AND THEIR SUCCESSION IN AGRO-ECOSYSTEM OF MANIPUR - SHANTIBALA, T.; SINGH, T. K.; SHAH, M. A. SATTAR (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2007)
The studies on insect pest complex and their succession conducted under the prevailing agro-climatic conditions of Manipur during 2004-2005 revealed that 19 insect pests belonging to 6 orders and 13 families were recorded to infest the pea crop. Jassid, (Empoasca sp.), aphid (Myzus persicae Sulzer) and semiloopers (Plusia signata Fabr., Thysanoplusia Orichalcea Fabr.) appeared first while pea pod borer (Lampides boeticus Linn.), thrip (Megaleurothrip distalis (Karny)) and pea aphid (Acrythosiphon pisum (Harris)) started infestation in the third and first week of December and January, respectively. Pea pod borer, thrip and pea aphid were recorded as the serious pest while M. persicae, semilooper and pea leaf miner, Phytomyza horticola Glover noticed as the moderate pests of pea.